Analysis of Leadership, Work Motivation, and Employee Competence Towards Customer Satisfaction with Employee Performance as an Intervening Variable in a Laptop Service Company at PT Rigroup Raya Sejahtera - Tari Pramanik; Gurawan Dayona Ismail; Aris Setiyani; Andhika Mochamad Siddiq (Eduvest - Journal of Universal Studies, 2026)
Customer satisfaction is a form of consumer evaluation or assessment of the performance of a product or service after use by comparing initial expectations and actual experiences obtained, resulting in feelings of satisfaction or dissatisfaction depending on the extent to which consumer needs and expectations are met or even exceeded. The purpose of this study is to determine the analysis of leadership, motivation, and competence on customer satisfaction with employee performance as an intervening variable. The research method used in this study is a quantitative research method with a descriptive and verification approach. Data collection techniques in this study are interviews, questionnaires, and observations with a population of 110 employees. The sampling technique used in this study is a non-probability sampling technique with purposive sampling. The analytical tool in this study is SmartPLS 4 for verification analysis. Testing of measurement models or outer models in this study is convergent validity, discriminant validity, Average Variance Extracted (AVE), composite reliability, Cronbach alpha. The structural model or inner models tested in this study were the coefficient of determination (R2) and predictive relevance (Q2). The results of this study indicate that leadership, motivation, and competence have a positive and significant effect on employee performance, both partially and simultaneously, with an influence of 84.2%, and the remaining 15.8% is influenced by other variables not examined in this study. Employee performance does not affect customer satisfaction, and employee performance cannot mediate the influence of leadership, motivation, and competence on customer satisfaction.